Impacto da enzima digestiva pepsina e eficácia preventiva do gel de partículas de vidro pré-reagido na erosão do esmalte com película adquirida - SILVA, Mayron Guedes (2024)
The increase in dental erosion in patients with Gastroesophageal Reflux Disease (GERD) highlights the importance of investigating the role of gastric acid enzymes in dental surface degradation. This study aims to evaluate, in vitro, the influence of pepsin on enamel erosion progression with acquired pellicle and the protective effect of a gel containing pre-reacted glass ionomer particles (S-PRG). Bovine dental enamel samples (6 x 6 x 2 mm) were prepared and standardized by measuring surface microhardness (SHbaseline). The samples were randomized into two experimental groups (n = 24): HCl (acidic hydrochloric acid erosive model, pH 2.0) and HCl+Pep (erosive model with pepsin, pH 2.0). Each group was subdivided based on treatments: SPRG [immersion in bioactive S-PRG gel; pH 6.4; 1:1 ratio (PRG Pro-Care Gel, Shofu)] and DW (deionized water – control, pH 6.4). To simulate the acquired pellicle, saliva from a healthy volunteer was collected, centrifuged, and used for daily immersion of the samples before erosive challenges (2h, pH 7.1). The erosive cycling model was conducted for 9 days, with daily immersions of the samples in acidic HCl solution (6 x 5 min), interspersed with artificial saliva (6 x 2 h). For treatments, each sample was immersed in 2 mL of the corresponding solution for 2 min, and all procedures were carried out with agitation at 100 rpm and 37°C. After 9 experimental days, microhardness (SHfinal) was measured, and surface hardness loss (%SHL) was calculated. Surface characterization included Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDS) to assess morphology and microchemical composition of enamel and the bioactive gel containing S-PRG particles. X-ray Diffraction (XRD) was performed to observe changes in the hydroxyapatite crystals of the treated blocks. Statistical analysis of %SHL data used one-way ANOVA followed by Tukey's post-hoc test (p < 0.05), with a significance level of 5%, while morphological and microchemical data were interpreted descriptively. The HCl+Pep group showed higher %SHL (p < 0.001) than the HCl group, and preventive exposure to the gel containing S-PRG particles did not significantly alter %SHL (p > 0.05). SEM images revealed intense mineral loss in the interprismatic regions of enamel in the HCl+Pep/DW group. HCl/SPRG showed regions with less structural degradation. XRD analysis revealed alterations in the microstructure of hydroxyapatite crystals, without significant recrystallization, and new crystalline phases, such as strontium-apatite and fluoroapatite, were detected in the S-PRG-treated groups. It is concluded that pepsin, combined with the erosive cycle, promotes greater surface microhardness loss of dental enamel, causing morphological degradation of the surface, changes in the microstructure of hydroxyapatite crystals, and reductions in calcium and phosphorus concentrations. Additionally, although the gel containing S-PRG particles facilitated the formation of OCP, the precursor of hydroxyapatite, it did not prevent the loss of enamel surface hardness.